INFLUENCE OF GENDER, BMI, AND ETHNICITY ON SERUM ALT LEVELS OF HEALTHY STUDENTS OF A MEDICAL SCHOOL - Bilal, Mohammad; Tariq, Areej; Khan, Somal; Quratulain, Quratulain; Tariq, Ayesha; Shahid, Muhammad Farooq; Khan, Muhammad Waqas; Shah, Aun Raza; Naveed, Abdul Khaliq (Journal of Ayub Medical College Abbottabad, 2011)
Background: Alanine Aminotransferase (ALT) is an enzyme found in Liver and indicates injury to Hepatocytes. It is influenced by various factors. The objectives of this study were to identify the correlates of ALT activity among healthy medical students of Army Medical College, National University of Sciences and Technology, aged 18-22 years. This was to establish the mean ALT levels of the students and compare them with those in various parts of the world and observe various correlations that exist and factors that may influence ALT levels. Methods: This population included 143 volunteer students (93 men and 50 women) selected on the basis of negative answers to a detailed medical questionnaire including past medical history, drug and alcohol consumption, on the absence of clinical signs of liver disease, on the negativity of serological testing for Hepatitis B and C virus. Results: The mean ALT level of the entire population was 28.7 IU/L. A major sex-difference in ALT value was observed, the mean ALT value being higher in men than in women (32.1±21.7 vs. 22.6±9.7 IU/L, p<0.004). According to WHO criteria for Asians, normal BMI was taken from 18.5-23.0 Kg/m2. There was a positive significant correlation between serum ALT level and BMI (p<0.002). ALT level strongly correlates with body mass index and gender. There was no significant variation in ALT levels among Punjabis and Sindhis, Balochis, Pathans, and Kashmiris. Conclusion: We suggest the need of taking into account these parameters in a clinical interpretation of ALT level. Keywords: ALT, Body Mass Index, BMI